Mastering Geography: Understanding how the‘Mastery Model’ can be used to assess Key Stage 3 Geography. - McKee, Catherine (2016)
This dissertation concerns the study and observations in a geography department in a Nottinghamshire secondary school academy and seeks to understand the utility of the Mastery Model in assessing Key Stage Three Geography. The Mastery Model is based on the ideas of Mastery Learning. Through the course of researching the Mastery Model, it became apparent that there were some limitations due in part to its effectiveness due to the wider political context of the dissertation. Therefore, a rubric was created by the author in order to mitigate the perceived limitations and create an assessment method that allows geography teachers to formatively assess students’ work with accuracy and integrity, and at the same time provide students with helpful and supportive feedback. The data includes observations of students using a rubric that were recorded in field notes, a reflective journal of the author’s experience using the Mastery Model and a focus group interview made up of four students that were part of the class trialling the Mastery Model rubric. The conclusions were that the Mastery Model did have limitations in assessing Key Stage Three Geography, but that the use of a rubric did mitigate some of these limitations. It was also an acceptable way of applying this assessment model as it provided students with high quality feedback on their work. The investigation also suggested that the use of the Mastery Model along with a rubric enabled both students and teachers to have a greater focus on the geographical understanding demonstrated by students, and not a distorted focus on the quality of written communication of the assessed piece of work.